Basal cell carcinoma of the lower eyelid affecting the lacrimal canaliculus and reconstruction with transposition flap and oral mucosa graft - Manoel Gomes; Solange Cardoso Maciel Silva (Sociedade Brasileira de Dermatologia (SBD), 2020)
The lower eyelid is one of the sites most affected by basal cell carcinoma (BCC). We present an option of inner corner skin flap with oral mucosa graft for eyelid reconstruction after BCC excision. This tumor affects approximately 60% of the lower eyelid and shows complete lower lacrimal canaliculus involvement. The use of internal corner skin transposition flap and oral mucosa graft is safe. The technique is reproducible and with good postoperative evolution. Positioning and eyelid movement were restored, allowing tear drainage through the upper canaliculus with complete correction of the tears' overflow (epiphora).